A Rational Choice Perspective in Economic Sociology - Коулман, Джеймс (Journal of Economic Sociology, 2010)
The paper provides unusual approach towards the sociology of rational choice. The author discusses the possibility to apply the theory for the explanation of economic problems not the sociological ones. It means that the author takes the economic instruments considering sociological aspects and applies to solve the economic theory problems. This statement let us assume that it is possible to divide clearly the economic issues from sociological ones but it was shown that this difference is rather washed out in reality.